Answers

2014-06-26T11:13:07+05:30
Use the remainder theorem for this question, that is, when any polynomial is to be divided by a linear polynomial in one variable, like here x-2, put the x-2 = 0, so x=2. Now, put x=2 in the polynomial to be divided . So, 10-4*2 + 3*2^2
=10-8+12 + 14
Hence, the remainder will be 14.
0
2014-06-26T11:15:46+05:30
Use the remainder theorem for this question, that is, when any polynomial is to be divided by a linear polynomial in one variable, like here x-2, put the x-2 = 0, so x=2. Now, put x=2 in the polynomial to be divided . So, 10-4*2 + 3*2^2
=10-8+12 + 14
0